2000
DOI: 10.1002/(sici)1097-4679(200001)56:1<33::aid-jclp4>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of psychosocial and physical risk factors in the causation of mammary cancer, and its prevention through psychological methods of treatment

Abstract: Some 8059 healthy women (mean age 58 years) were studied in 1973 with the aim of establishing the presence or absence of a variety of physical and psychological risk factors for mammary cancer. Mortality was established in 1988,15 years later. Both physical and psychological risk-*Deceased-9/4/97, London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 63 publications
(64 reference statements)
0
22
0
4
Order By: Relevance
“…Whereas stressful events do not appear to occur more often among those in whom cancer later developed, 21 41% of respondents in another study 22 cited stress as a cause of cancer. Neither the results on depression and immune function, 23 nor the findings related to psychological factors such as stress in cancer initiation 21,24,25 offer evidence for a role in cancer etiology. For causes commonly mentioned both by these patients with cancer and in the literature, the relative importance of categories varied dramatically.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas stressful events do not appear to occur more often among those in whom cancer later developed, 21 41% of respondents in another study 22 cited stress as a cause of cancer. Neither the results on depression and immune function, 23 nor the findings related to psychological factors such as stress in cancer initiation 21,24,25 offer evidence for a role in cancer etiology. For causes commonly mentioned both by these patients with cancer and in the literature, the relative importance of categories varied dramatically.…”
Section: Discussionmentioning
confidence: 96%
“…Such synergistic risks can vary greatly in magnitude and have been identified for a range of hazard combinations across several domains. ( 1‐5 ) However, much less is known about lay individuals' understanding of synergistic risks.…”
Section: Introductionmentioning
confidence: 99%
“…( 1,22 ) Synergistic risks not only arise from physical interactions, but also from interactions involving psychological, environmental, and physiological factors. ( 2,4,23‐25 ) For example, Raine et al ( 5 ) show that the likelihood of a male committing a violent crime before reaching adulthood increases synergistically if his birth involved medical complications (e.g., mother suffering from preeclampsia) and he is subject to maternal rejection. Hence, there is increasing evidence that synergistic risks are not unique to the interaction of physical hazards.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis by Duijts et al (2003) found that approximate measures of stress, such as number of stressful life events, death of a significant other, and death of a loved one are correlated to breast cancer risk by odds ratios of 1.77 (95% confidence interval: 1.31–2.40), 1.37 (95% CI: 1.10–1.71), and 1.35 (95% CI: 1.09–1.68), respectively. Similarly, recent prospective cohort studies (Grossarth‐Maticek et al, 2000; Lillberg et al, 2001, 2002; Helgesson et al, 2003) show a significant association between approximate measures of psychological stress and breast cancer risk. Explaining this correlation requires the elucidation of a coherent biological mechanism able to link these two processes.…”
Section: Introductionmentioning
confidence: 76%